2017
DOI: 10.1002/jaal.631
|View full text |Cite
|
Sign up to set email alerts
|

Picturing Ethnic Studies: Photovoice and Youth Literacies of Social Action

Abstract: Chicanx students use photovoice to articulate the importance of their high school ethnic studies course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…This article extends the bodies of literature that point to the potential of digital media tools to amplify civic participation (Kahne & Bowyer, 2019;Mirra & Garcia, 2017) as well as the uptake of technology and digital literacies in Ethnic Studies classrooms (de los Ríos, 2017Ríos, , 2018.…”
Section: Critical Digital Literacies Activist New Media and Criticamentioning
confidence: 65%
“…This article extends the bodies of literature that point to the potential of digital media tools to amplify civic participation (Kahne & Bowyer, 2019;Mirra & Garcia, 2017) as well as the uptake of technology and digital literacies in Ethnic Studies classrooms (de los Ríos, 2017Ríos, , 2018.…”
Section: Critical Digital Literacies Activist New Media and Criticamentioning
confidence: 65%
“…Ethnic studies courses encompass and amplify fundamental sociocultural and sociopolitical experiences, where students are encouraged to make sense of their intersectional lives on both personal and structural levels. As secondary ethnic studies courses continue to proliferate with the support of California Assembly Bill 2016, a recently passed legislation that sanctions ethnic studies courses throughout California's school districts, this research contributes to the scant but necessary scholarship about the decolonial possibilities of literacy activity within these classrooms (de los Ríos, 2017a(de los Ríos, , 2017b.…”
Section: Discussionmentioning
confidence: 98%
“…Critics have argued that ethnic studies courses, including its subdisciplines such as Chicanx/Latinx Studies courses, promote racial separatism and do not equip students with academic literacy skills (Martinez, 2012;Planas, 2012). However, growing research has demonstrated that ethnic studies courses foster robust academic literacy development and empowered transnational youth identity development (de los Ríos, 2013(de los Ríos, , 2016(de los Ríos, , 2017b. Moreover, as increasing antiimmigrant rhetoric rises under the current presidential administration, the grassroots movement to expand secondary ethnic studies courses is gaining momentum in some of the most racially and linguistically diverse California school districts (Buenavista, 2016).…”
Section: Sociopolitical Context Of the Studymentioning
confidence: 99%
See 2 more Smart Citations